2011
DOI: 10.1017/s0022149x11000691
|View full text |Cite
|
Sign up to set email alerts
|

First report of a gryporhynchid tapeworm (Cestoda: Cyclophyllidea) from New Zealand and from an eleotrid fish, described from metacestodes andin vitro-grown worms

Abstract: Metacestodes are often found in the body cavity of the common bully (Gobiomorphus cotidianus McDowall), from freshwater habitats in Otago, New Zealand. Identification of metacestodes relies only on the number, size and shape of the rostellar hooks. To attempt species determination, we cultivated metacestodes in vitro for up to 23 days, during which they matured to at least the male stage of development, although female organs were not discernable. Identified as members of the genus Paradilepis Hsü, 1935 (famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…is most closely related to species from Australia. This pattern is seen in several species of parasitic helminth (Presswell et al , 2012; Cribb et al , 2014b; Georgieva et al , 2017; Huston et al , 2018), and is perhaps unsurprising when considering that Australia is the closest large land mass and much of New Zealand's marine avifauna has evolved from Australian immigrant species or vice versa (e.g. Diamond, 1984; Given et al , 2005).…”
Section: Discussionmentioning
confidence: 98%
“…is most closely related to species from Australia. This pattern is seen in several species of parasitic helminth (Presswell et al , 2012; Cribb et al , 2014b; Georgieva et al , 2017; Huston et al , 2018), and is perhaps unsurprising when considering that Australia is the closest large land mass and much of New Zealand's marine avifauna has evolved from Australian immigrant species or vice versa (e.g. Diamond, 1984; Given et al , 2005).…”
Section: Discussionmentioning
confidence: 98%
“…As adults, gryporhynchids parasitize the intestines of fish-eating birds across the globe. Recently, molecular and morphological phylogenetic hypotheses showed that the family Gryporhynchidae is a monophyletic group nested within the Cyclophyllidea (Mariaux, 1998; Hoberg et al ., 1999a; Presswell et al ., 2012; Mariaux et al , 2017), but these studies were based on a few species. The phylogeny inferred in the present study includes a much greater diversity of gryporhynchids (20 species representing 9 of 16 described genera).…”
Section: Discussionmentioning
confidence: 99%
“…We used the software Clustal W (Thompson et al ., 1997) for the alignment of the sequences of species of adult gryporhynchid tapeworms and for the species Paradilepis cf. minima (SSU; larva from fish – see Presswell et al ., 2012); Amirthalingamia macracantha (Joyeux & Baer, 1975); Neogryporhynchus lasiopeius Baer & Bona, 1960; Paradilepis maleki Khalil, 1961; Paradilepis scolecina (Rudolphi, 1819); Paradilepis sp. ; Parvitaenia sp.…”
Section: Methodsmentioning
confidence: 99%
“…Adults of the genus Paradilepis Hsü, 1935 are parasites of Pelecaniformes and, in many cases, cormorants (Presswell et al, 2012). It consists of fourteen species, Paradilepis delachauxi Fuhrmann, 1909, Paradilepis diminuta Huey & Dronen, 1981, Paradilepis kempi Southwell, 1921, Paradilepis longivaginosus Mayhew, 1925, Paradilepis maleki Khalil, 1961, Paradilepis urceina Bona, 1975, Paradilepis phalacrocoracis Ukoli, 1968, Paradilepis minima Goss, 1914, Paradilepis patriciae Baer & Bona, 1960, Paradilepis rugovaginosus Freeman, 1954, Paradilepis scolecina Rudolphi, 1819, Paradilepis simoni Rausch, 1949, Paradilepis urceus Wedl, 1855, and P. caballeroi (Presswell et al, 2012.…”
Section: P Caballeroimentioning
confidence: 99%